A systematic review and net meta-analysis of the effects of different warm-up methods on the acute effects of lower limb explosive strength - F. Y. Li; C. G. Guo; H. S. Li; H. R. Xu; P. Sun (BMC, 2023)
Abstract Objective To evaluate the effects of different warm-up methods on the acute effect of lower limb explosive strength with the help of a reticulated meta-analysis system and to track the optimal method. Methods R software combined with Stata software, version 13.0, was used to analyse the outcome metrics of the 35 included papers. Mean differences (MD) were pooled using a random effects model. Results 1) Static combined with dynamic stretching [MD = 1.80, 95% CI: (0.43, 3.20)] and dynamic stretching [MD = 1.60, 95% CI: (0.67, 2.60)] were significantly better than controls in terms of improving countermovement jump height (cm), and the effect of dynamic stretching was influenced by the duration of stretching (I2 = 80.4%), study population (I2 = 77.2%) and age (I2 = 75.6%) as moderating variables, with the most significant effect size for dynamic stretching time of 7-10min. 2) Only dynamic stretching [MD = -0.08, 95% CI: (-0.15, -0.008)] was significantly better than the control group in terms of improving sprint time (s), while static stretching [MD = 0.07, 95% CI: (0.002, 0.13)] showed a significant, negative effect. 3) No results were available to demonstrate a significant difference between other methods, such as foam axis rolling, and the control group. Conclusion The results of this review indicate that static stretching reduced explosive performance, while the 2 warm-up methods, namely dynamic stretching and static combined with dynamic stretching, were able to significantly improve explosive performance, with dynamic stretching being the most stable and moderated by multiple variables and dynamic stretching for 7-10min producing the best explosive performance. In the future, high-quality studies should be added based on strict adherence to test specifications.